Evaluation of Performance of Mutual Funds in India from 2000 to 2007 - Saboo, Manish (2008)
There have been many studies in the past on performance of Mutual Funds in comparison to the market. These studies might differ in time and the market under study but most of them concluded that on an average, Mutual Funds have failed to outperform the market and thus the Efficient Market Hypothesis holds good. This research was based on performance of 22 mutual funds for a period of almost 8 years on monthly basis. Funds were evaluated using measures like Sharpe ratio, Treynor ratio, Jensen's Alpha, Information Ratio, Expense Ratio etc. The results were quite surprising as 15 out of 22 mutual funds have utperformed the market index i.e. in our case BSE 500.